Field trials testing material composition and surface complexity and the effects on benthic faunal recruitment at a cold-water coral reef site - Strömberg, Susanna M.; Larsson, Ann I. (Frontiers in Environmental Science, 2025)
Reef habitats of the cold-water coral Desmophyllum pertusum in the Skagerrak have been damaged until near extinction by bottom trawling and other anthropogenic impacts over the last decades. There is, however, one site with a thriving reef that brings hope for potential recovery. A large-scale restoration project has been launched, and to find the optimal material composition for the artificial reefs to be deployed we tested three concrete mixes against standard Portland cement as controls, and two different surface textures with different levels of complexity in a field settling experiment. The mixed concrete panels had different ratios of ground granulated blast furnace slag and silica oxide added, components that have been shown to increase compressive strength and longevity of concrete in the marine environment. Panels were deployed close to a live reef site and left submerged for 19 months. Recruitment of reef associated fauna was generally high on all panels. Surface complexity had a significant effect on diversity and species richness, with higher values on the more complex substrates. The position of the panels (side and level above seafloor) was associated with a significant effect on coverage, diversity, and richness. The concrete mix had less effect on coverage and diversity of associated fauna, however, panels with the highest level of added silica oxide had significantly lower values. No recruitment of D. pertusum larvae were observed. The results show that surface complexity is more important than material composition for the recruitment of benthic invertebrates, and one can therefore put more focus on complexity and material durability when constructing artificial reefs.